Diversité Floristique Des Ligneux Et Structure Des Formations À Garcinia Kola Heckel Dans Les Régions Du Centre Et De l’Est, Cameroun - Borel, Kamga Yanick; François, Nguetsop Victor; Caroline, Momo Solefack Marie; Bernard, Riera (European Scientific Journal, ESJ, 2018)
In order to find the strategies to ensure the sustainable management of natural’s resources and especially woody plants in the Congo Basin, a study was carried out on the floristic diversity of woody plants and the structure of Garcinia kola formations in the Centre and East regions of Cameroon. A total of 39 quadrats of 40 m x 40 m were installed in the Garcinia kola formations in these two regions. In each plot, we identified and counted all individuals with a dbh ≥ 10 cm. Seedlings of G. kola (dbh<10 cm) were also counted in all the plots. The height and diameter of each individual were measured. ANOVA was used to compare the density averages of the different plots, and the DUNCAN test at 5% significance level (XLSTAT 2017) was used to separate these mean values. This study confirms that the Clusiaceae (G. kola) forms the floristic background of the stand studied. The surveys revealed a total of 196 species, 156 species (H ’= 2.98) and 68 species (H’ = 2.13), respectively, identified in the East and Centre among the population of individuals showing dbh ≥ 10 cm. They were distributed into 124 genera and 46 families. The most diversified families in G. kola formations are Euphorbiaceae, Fabaceae, Meliaceae, Sterculiaceae, Moraceae, Anacardiaceae, Apocynaceae, Annonaceae, Rutaceae, Rubiaceae, and Clusiaceae. The average standing density of G. kola varies from 6.51 (East Region) to 40.72 (Centre Region) stems per hectare. The low density observed in the localities of the eastern region can be explained by the pressure exerted on this species in the natural environment linked mostly to methods of exploitation.